From negative to positive: two-sided messages and the effect of involvement - Cleve, Moritz (Kansas State University, 2015)
Two-sided message research has often led to ambiguous findings due to several factors. The present study examines if the level of general involvement with the product category presented in the persuasive message influences whether or not the inclusion of unfavorable information can generate positive effects on source credibility, brand attitude, and behavioral intent. Past studies on the effects of involvement on sidedness failed to deliver clear results, due to vague operationalizations, irrelevant claims and message statements. A 3 (sidedness: one-sided, two-sided unrelated attributes, or two-sided related attributes) x 2 (involvement: low or high) factorial design was used for this study. Contrary to past research, this study indicates that two-sided messages have many facets. Although a main effect for two-sided messages over one-sided ones was present, findings indicate nearly all of the benefits associated with two-sided messages were due the relatedness of the negative information claim. Two-sided messages without relatedness of information performed no differently than the one-sided format.
Keywords: two-sided messages; advertising; marketing; involvement; mass communications; persuasion; Mass Communications (0708)